2020
DOI: 10.21182/jmisst.2019.00073
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Minimally Invasive Transforaminal Lumbar Interbody Fusion in Elderly

Abstract: The purpose of this study was to compare the clinical-radiological outcome and incidence of perioperative complications of MIS-TLIF at lower lumbar levels for elderly (Age >65 years) and younger patients (Age<65 years). Methods: A retrospective cohort study performed from 2011 to 2017. A total 138 patients who underwent MIS-TLIF were divided into two groups based on age (group A>65 years and group B<65 years). Perioperative clinical (co-morbidities, surgical time, blood loss, hospital stay, fusion level, VAS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…1). [20][21][22][23][24][25][26][27][28][29][30][31] Two studies performed prospective data collection and analysis, 21,29 whereas the remaining 10 performed retrospective analyses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). [20][21][22][23][24][25][26][27][28][29][30][31] Two studies performed prospective data collection and analysis, 21,29 whereas the remaining 10 performed retrospective analyses.…”
Section: Resultsmentioning
confidence: 99%
“…27 Studies defined elderly patients variably. The most common cutoff age was 65 years (7 studies, 58%), [22][23][24][25][26]28,30 followed by 70 years (3 studies, 25%). 20,21,31 One study used an 80-year cutoff, 27 and the remaining study divided the patient cohort into age groups of equal size, which resulted in a cutoff age of 66 years.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical outcomes of MIS-TLIF is highly impacted by aging; however, a recent retrospective study in the elderly (>65 years) and younger (<65 years) patients revealed significant improvements in both groups with no significant difference in blood loss, hospitalization stay time period, mobilization, and ODI, VAS, and Wang’s score. This indicate that the aging is not a deterrent to outcome and should not be considered as a contraindication to perform MIS-TLIF in the older population [ 88 ]. In another retrospective study, the efficacy of grade 1 fusion and complication rates were identical in middle- and old-aged patients at the end of 2-year follow-up [ 89 ].…”
Section: Mis–tlif: the Surgical Proceduresmentioning
confidence: 99%